2016
DOI: 10.1063/1.4954882
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the anions on the N-cationic benzethonium salts in the solid state and solution: Chloride, bromide, hydroxide and citrate hydrates

Abstract: The crystal structures of the hydrated cationic surfactant benzethonium (Bzth) chloride, bromide, hydroxide, and citrate have been determined by X-ray diffraction analysis and compared with their structures in solution well above their critical micelle concentration. The differences in the nature of the various anions of the four Bzth-X materials lead to unique anion environments and 3-D molecular arrangements. The water molecule in the monoclinic Bzth-Cl or Bzth-Br forms is hydrogen bonded to the halides and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…ity against head and neck cancer [1][2][3], BZT is used in numerous pharmaceutical formulations as: active ingredient for antiseptics e.g. topical anti-infective in veterinary medicine, [4][5][6][7], many fungi and lipid-containing viruses are susceptible to BZT [8] and was also found as efficient non-viral reagent gene vectors due to their safety and other inherent properties over viral delivery techniques to transfect outer DNA into animal cells in vitro [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…ity against head and neck cancer [1][2][3], BZT is used in numerous pharmaceutical formulations as: active ingredient for antiseptics e.g. topical anti-infective in veterinary medicine, [4][5][6][7], many fungi and lipid-containing viruses are susceptible to BZT [8] and was also found as efficient non-viral reagent gene vectors due to their safety and other inherent properties over viral delivery techniques to transfect outer DNA into animal cells in vitro [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The SAXS profile for the oil-free BCl control was not analyzed using the ellipsoidal model for two reasons, first that the signal was too noisy to have well-defined features, and second the uncertainty in assigning a well-defined headgroup. While we have highlighted the quaternary ammonium group for BCl in Figure 9, the only previous BCl-SAXS study found in the literature suggests that the phenyl group, the ethoxy groups, and bound water form a headgroup environment that has a different electron distribution from other well-defined quaternary cationic surfactants 34 . One other important feature in Figure 9 is that the right-side exponent of the transition fit is nR = -2, suggesting that the Teubner-Strey model is still relevant for these systems; however, as indicated in the fit summary in Table S9, the system prepared with 0.1% NaCl (ln(S)= -1.36) has an nR= -1.43.…”
Section: Saxs-based Determination Of CC For Benzethonium Chloride (Bcl)mentioning
confidence: 76%